2006
DOI: 10.1209/epl/i2005-10433-3
|View full text |Cite
|
Sign up to set email alerts
|

Cryogenic microjet for exploration of superfluidity in highly supercooled molecular hydrogen

Abstract: We describe a new approach to producing a sample of supercooled molecular para-hydrogen (pH2) at temperatures down to 1.3 K, well below the predicted superfluid transition temperature for pH2. Unique features of the present scheme are 1) the suppression of both homogeneous and heterogeneous nucleation processes and 2) the possibility to control the liquid temperature in a wide range across the transition. As a first step we demonstrate the stable production in vacuum of continuous hydrogen filaments of macrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
26
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 21 publications
2
26
0
Order By: Relevance
“…2,11 On the other hand, diffusion Monte Carlo ͑DMC͒ T = 0 calculations indicate that N = 13 and possibly 19 and 33 are magic and energetically more stable than the neighboring sizes, consistent with the clusters being solidlike. 10,13,17 PIMC calculations at 0.5Յ T Յ 4.5 K indicate also that N = 19,23,26,29,32, and 37 clusters are magic in agreement with icosahedral magic numbers expected for solid clusters. 14,16 Other PIMC calculations suggest that below about 0.75-0.25 K the quantum delocalization is greatly enhanced 19,20 favoring superfluidity.…”
Section: Introductionsupporting
confidence: 65%
“…2,11 On the other hand, diffusion Monte Carlo ͑DMC͒ T = 0 calculations indicate that N = 13 and possibly 19 and 33 are magic and energetically more stable than the neighboring sizes, consistent with the clusters being solidlike. 10,13,17 PIMC calculations at 0.5Յ T Յ 4.5 K indicate also that N = 19,23,26,29,32, and 37 clusters are magic in agreement with icosahedral magic numbers expected for solid clusters. 14,16 Other PIMC calculations suggest that below about 0.75-0.25 K the quantum delocalization is greatly enhanced 19,20 favoring superfluidity.…”
Section: Introductionsupporting
confidence: 65%
“…However, recent experiments have indicated that, even at T ∼ 9 K, the rate of crystal growth is so high that the liquid phase freezes quickly into a metastable polymorph crystal. 10 Even though several supercooling techniques have been proposed to create a metastable liquid phase in bulk p-H 2 , [11][12][13] none of them has proven so far to be successful and no direct evidence of superfluidity has been detected. However, there are evidences of superfluidity in several spectroscopic studies of small doped p-H 2 clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Other attempts of producing liquid p-H 2 well below T f (T = 1.3 K) are based on the generation of continuous hydrogen filaments of macroscopic dimensions. 13 The search for a superfluid p-H 2 phase has been intense also from the theoretical point of view. The rather simple radial form of the p-H 2 -p-H 2 interaction and the microscopic accuracy achieved by quantum Monte Carlo methods have stimulated a long-standing effort for devising possible scenarios where supercooled p-H 2 could be studied.…”
Section: Introductionmentioning
confidence: 99%
“…However, hydrogen molecules have van der Waals interactions, which are 12 times stronger than those between helium atoms and, in bulk, hydrogen solidifies at 13.8 K. The -temperature for parahydrogen has been estimated from the Bose-Einstein condensation temperature to be ϳ6 K. 10 All other forms of the hydrogen molecule ͑ortho-H 2 , para-D 2 , and ortho-D 2 ͒ are expected to have the transition occur at lower temperatures because of the degeneracy of their lowest energy level. 10 Many experiments have been made to supercool bulk hydrogen to produce a superfluid, [10][11][12][13][14] but all attempts have been unsuccessful. Gas-phase studies, where solidification may not be an issue, could potentially demonstrate the onset of superfluidity in hydrogen clusters.…”
Section: Introductionmentioning
confidence: 99%
“…measured of clusters containing OCS, O13 CS, and OC 34 S, as well as O 13 C 34 S for the ͑o-H 2 ͒ 2 -OCS cluster. The signal intensity of the clusters was sufficient to observe the J K a K c =1 01 −0 00 transition of ͑p-H 2 ͒ 2 -OCS with 10 averaging cycles.…”
mentioning
confidence: 99%